Accidental deaths & suicides in India - National Crime Records Bureau (New Delhi, 2011)
Accidents (man-made and natural) and suicides are among the two most important reasons for pre-mature end to human lives. Injuries resulting from the accidents handicap many people. These unfortunate victims are important members of their families as well as of the society. As a result, the loss on account of accidents and suicides is felt by the family members and society at large. The profound and extensive impact of accidents and suicides makes it imperative for the society to make earnest. efforts at reducing the incidence of these phenomena. In this context, exhaustive database on accidents and suicides is of utmost importance to carry out any meaningful study and for making informed policy decisions. It is hoped that the policy makers, law enforcement agencies, government departments, researchers, media and NGOs will be benefited from the data contained in this publication. The previous editions of this publication are available on the website of NCRB.
Keywords: Accidental deaths